Resistance to Quinupristin-Dalfopristin Due to Mutation of L22 Ribosomal Protein in Staphylococcus aureus - Malbruny, Brigitte (American Society for Microbiology, 2002)
The mechanism of resistance to the streptogramin antibiotics quinupristin and dalfopristin was studied in a Staphylococcus aureus clinical isolate selected under quinupristin-dalfopristin therapy, in four derivatives of S. aureus RN4220 selected in vitro, and in a mutant selected in a model of rabbit aortic endocarditis. For all strains the MICs of erythromycin, quinupristin, and quinupristin-dalfopristin were higher than those for the parental strains but the MICs of dalfopristin and lincomycin were similar. Portions of genes for domains II and V of 23S rRNA and the genes for ribosomal proteins L4 and L22 were amplified and sequenced. All mutants contained insertions or deletions in a protruding β hairpin that is part of the conserved C terminus of the L22 protein and that interacts with 23S rRNA. Susceptible S. aureus RN4220 was transformed with plasmid DNA encoding the L22 alteration, resulting in transformants that were erythromycin and quinupristin resistant. Synergistic ribosomal binding of streptogramins A and B, studied by analyzing the fluorescence kinetics of pristinamycin I(A)-ribosome complexes, was abolished in the mutant strain, providing an explanation for quinupristin-dalfopristin resistance.